Using Discharge Abstracts to Evaluate a Regional Perinatal Network: Assessment of the Linkage Procedure of Anonymous Data - Catherine Quantin; Cyril Ferdynus; Paul Avillach; Béatrice Gouyon; Paul Sagot; Jean-Bernard Gouyon (International Journal of Telemedicine and Applications)
To assess the Burgundy perinatal network (18 obstetrical units; 18 500 births per year), discharge abstracts and additional data were collected for all mothers and newborns. In accordance with French law, data were rendered anonymous before statistical analysis, and were linked to patients using a specific procedure. This procedure allowed data concerning each mother to be linked to those for her newborn(s). This study showed that all mothers and newborns were included in the regional database; the data for all mothers were linked to those for their infant(s) in all cases. Additional data (gestational age) were obtained for 99.9% of newborns.